2021
DOI: 10.3390/vision5020020
|View full text |Cite
|
Sign up to set email alerts
|

Visual Perception in Migraine: A Narrative Review

Abstract: Migraine, the most frequent neurological ailment, affects visual processing during and between attacks. Most visual disturbances associated with migraine can be explained by increased neural hyperexcitability, as suggested by clinical, physiological and neuroimaging evidence. Here, we review how simple (e.g., patterns, color) visual functions can be affected in patients with migraine, describe the different complex manifestations of the so-called Alice in Wonderland Syndrome, and discuss how visual stimuli can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 105 publications
0
5
0
Order By: Relevance
“…The visual aura might also manifest as a temporary loss of vision [6], though binocular blindness among migraineurs is a rare occurrence. Temporary binocular blindness usually presents in people with migraine as a single, isolated, totally reversible episode and is not related to other symptoms of aura [7]. Finally, after diagnostics, it was stated that the patient's episodes of visual impairment corresponded with a recurrent migraine aura and were the equivalent of altitude-induced migraine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The visual aura might also manifest as a temporary loss of vision [6], though binocular blindness among migraineurs is a rare occurrence. Temporary binocular blindness usually presents in people with migraine as a single, isolated, totally reversible episode and is not related to other symptoms of aura [7]. Finally, after diagnostics, it was stated that the patient's episodes of visual impairment corresponded with a recurrent migraine aura and were the equivalent of altitude-induced migraine.…”
Section: Discussionmentioning
confidence: 99%
“…The visual aura might also manifest as a temporary loss of vision [6], though binocular blindness among migraineurs is a rare occurrence. Temporary binocular blindness usually presents in people with migraine as a single, isolated, totally reversible episode and is not related to other symptoms of aura [7].…”
Section: Discussionmentioning
confidence: 99%
“…Scintillating scotoma and blurry vision are the most frequent visual symptoms in children, followed by tunnel vision and zig-zag lines [ 20 ]. Moreover, most frequently than adults, children complain of color dysgnosia caused by unusual color brightness that prevents patients from recognizing color shades [ 20 , 21 ]; less frequently, adult patients complain of dimmed colors or achromatopsia, usually often associated with both prosopagnosia and loss of spatial orientation [ 22 ]. Theoretically, color perception changes could result from photophobia or a direct migraine effect on color processing, as Noseda et al suggested, originating in the retina and thalamus rather than in cortical visual processing areas [ 23 ].…”
Section: Visual Symptoms In Migrainementioning
confidence: 99%
“…The visual cortex is another notable cortical region that has vital role in the ascending trigeminovascular pathway, with implications in the pathophysiological mechanism of migraine (Marzoli & Criscuoli, 2017). Correspondingly, functional abnormalities in the visual cortex, notably the LG, are not only associated with the clinical characteristics of migraine (Tedeschi et al, 2016) but also represent a critical neuropathological feature (Hadjikhani & Vincent, 2021). Furthermore, cognitive behavioural therapy-induced functional alterations in the LG, a region involved in nociceptive processing, may aid in preventing migraine headaches (Nahman Averbuch et al, 2020).…”
Section: Response Groupmentioning
confidence: 99%